Confusion matrix for features: [‘speech_speed’, ‘avg_characters’, ‘adj_freq’, ‘how are you at controlling your temper’] with n_estimators = 300. - Giuliano Lorenzoni (21440268) (2025)
Confusion matrix for features: [‘speech_speed’, ‘avg_characters’, ‘adj_freq’, ‘how are you at controlling your temper’] with n_estimators = 300.